Telephone interpreting for asylum seekers in the US: a corpus-based study - Amparo Jiménez-Ivars (JoSTrans: The Journal of Specialised Translation)
This paper addresses the asylum seekers' right to language access and specifically the provision of telephonic interpreting services for people crossing the US southern border. An overview of the language access situation is presented in relation to basic asylum seekers' rights. The fundamentals of interpreting professionalism in this realm are also reviewed. The study aim is to examine interpreters' perceptions of their work environment as contractors for the two major language service providers working with the US Immigration and Customs Enforcement agency and the US Department of Homeland Security. For this purpose, a corpus study was conducted based on online reviews posted on job search engines by current or past interpreter contractors. Findings identify perceptions of several inadequate management practices that negatively affect the work environment, job satisfaction and professional demands in terms of required qualifications, testing, training and supervision. The flaws observed point to an absence of the professional standards and motivation required to enable quality performance and therefore, professionalism. A proposal to offer professional services by engaged citizens is made.